1982
DOI: 10.4315/0362-028x-45.12.1120
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response of an Osmotolerant Sorbate-Resistant Yeast, Saccharomyces rouxii, at Different Sucrose and Sorbate Levels

Abstract: Effects of preconditioning Saccharomyces rouxii to various sucrose and sorbate concentrations were investigated. Cells were preconditioned to 0 and 60% (wt/vol) sucrose without and with 0. 1% (wt/vol) sorbate by a series of four transfers in potato dextrose broth (PDB). The preconditioned cells were inoculated in growth medium containing 0, 30, or 60% (wt/vol) sucrose with 0. 0.05, or 0.1% (wt/vol) sorbate and in chocolate syrup without and with 0.1% (wt/vol) sorbate. Preconditioning of S. rouxii cells to 0 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Anyhow, it must be highlighted that nowadays consumers demand products free of chemical preservatives or with reduced levels of them. For these reasons, it is important to study the effect of other addtives on antimicrobial action; as an example, elevated salt or sugar concentration and pH depression were shown to act synergistically enhancing sorbates action (Bills, Restaino, & Lenovich, 1982;Praphailong & Fleet, 1997;Castro, Garro, Campos, & Gerschenson, 2002) and allowing to use reduced levels with equal effect.…”
Section: Introductionmentioning
confidence: 98%
“…Anyhow, it must be highlighted that nowadays consumers demand products free of chemical preservatives or with reduced levels of them. For these reasons, it is important to study the effect of other addtives on antimicrobial action; as an example, elevated salt or sugar concentration and pH depression were shown to act synergistically enhancing sorbates action (Bills, Restaino, & Lenovich, 1982;Praphailong & Fleet, 1997;Castro, Garro, Campos, & Gerschenson, 2002) and allowing to use reduced levels with equal effect.…”
Section: Introductionmentioning
confidence: 98%
“…The minimum a, range in a fructose syrup at pH 4.8 and in glucose (von Schelhorn, 1950;Tilbury, 1976) broths was 0.62 to 0.65, whereas in NaCl, a minimal value for growth of 0.86 has been reported (Onishi, 1963). The type solute used to reduce a, of growth media influenced both amount and rate of mngal growth (Anand and Brown, 1968;Warth, 1986) as well as growth response to antimicrobials (Bills et al, 1982, Lenovitch et al, 1988. The a, adjusted with a mixture sucroseglycerol (35) affected the growth of Z. rouxii at pH 4.0 and 28°C Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Warth (1977) observed that Z. bailii grown in the presence of sorbic acid displayed increased resistance upon subsequent exposure to the compound, compared to unexposed cells. Bills and others (1982) found that pre‐exposure of Saccharomyces rouxii to sorbic acid significantly increased resistance to the agent, as seen in shorter lag times and/or shorter time to stationary phase, compared with previously unexposed cells. One mechanism for the resistance acquired by the yeasts is induction of an inducible, energy‐requiring system that increases sorbic acid efflux (Bills and others 1982; Warth 1977).…”
mentioning
confidence: 91%
“…Bills and others (1982) found that pre‐exposure of Saccharomyces rouxii to sorbic acid significantly increased resistance to the agent, as seen in shorter lag times and/or shorter time to stationary phase, compared with previously unexposed cells. One mechanism for the resistance acquired by the yeasts is induction of an inducible, energy‐requiring system that increases sorbic acid efflux (Bills and others 1982; Warth 1977). However, resistance of yeasts to sorbic acid and other weak acids probably involves more than one system (Brul and Coote 1999).…”
mentioning
confidence: 91%